Competitive Preferences among Asians in the U.S. - John Ifcher; Homa Zarghamee (Institute of Labor Economics (IZA), 2020)
The median income of Asian households is the highest of all racial/ethnic groups in the U.S. In a laboratory experiment, we examine whether Asians are more willing to compete and have greater competitive preferences than non-Asians. Both with and without controls for performance, performance improvement, and confidence, we find that Asians have significantly greater competitive preferences than non-Asians.
Keywords: J15; L0; 330; race/ethnicity; Asian; identity; norm; competitive preferences; willingness to compete